No Place Like Home? An Identity Strain Perspective on Repatriate Turnover - Kraimer, Maria L.; Shaffer, Margaret A.; Harrison, David A.; Ren, Hong (Academy of Management Journal, 2012)
We draw on identity theory to explain why employees returning from international assignments may leave their organizations. We tested our predictions over a 12-month period with a sample of 112 repatriated employees from a broad cross-section of firms. Prior job embeddedness during expatriation positively relates to the strength of an individual's identity as an international employee in repatriation. This creates identity strain when a repatriate perceives job deprivation relative to noninternational peers. Identity strain, in turn, promotes turnover. We discuss how this perspective contributes to theory on international role transitions, job embeddedness, and turnover mechanisms in general.